Literacy : an international handbook - Wagner, Daniel A.; Venezky, Richard L.; Street, Brian V. (Boulder, Colo : Westview Press, 1999)
A collection of articles by noted authorities about literacy from an historical viewpoint as well as current perspectives
Includes bibliographical references and indexes.
Keywords: Literacy -- Handbooks, manuals, etc; Language arts -- Handbooks, manuals, etc